Application of electrolyzer system to enhance frequency stabilization effect of microturbine in a microgrid system - Vachirasricirikul, Sitthidet; Ngamroo, Issarachai; Kaitwanidvilai, Somyot (My University, 2009)
It is well known that the power output of microturbine can be controlled to compensate for load change and alleviate the system frequency fluctuations. Nevertheless, the microturbine may not adequately compensate rapid load change due to its slow dynamic response. Moreover, when the intermittent power generations from wind power and photovoltaic are integrated into the system, they may cause severe frequency fluctuation. In order to study the fast dynamic response, this paper applies electrolyzer system to absorb these power fluctuations and enhance the frequency control effect of microturbine in the microgrid system. The robust coordinated controller of electrolyzer and microturbine for frequency stabilization is designed based on a fixed-structure H∞ loop shaping control. Simulation results exhibit the robustness and stabilizing effects of the proposed coordinated electrolyzer and microturbine controllers against system parameters variation and various operating conditions. Crown Copyright © 2009.
Keywords: Electrolyzer system; Frequency stabilization; H∞ loop shaping control; Microgrid; Microturbine; Particle swarm optimization